Pathways of Peace: Discovering Unity Through the Pilgrimage to Indonesia's Maria Caves - Satrya, I Dewa Gde; Wono, Hilda Yunita; Kaihatu, Thomas S; Minantyo, Hari (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2024)
Catholics in Indonesia have a long tradition of making pilgrimages to the Gua Maria (Maria Caves), complementing visits to cathedrals and other religious sites. This study focuses on Marian tourism at the Gua Maria in Java and Bali, highlighting their inclusivity as destinations open to both Catholic and non-Catholic visitors, fostering peace and mutual respect. The research explores the spiritual and communal experiences of pilgrims, investigating the interplay between religious practices and tourist behaviour in a multicultural context. Using a qualitative approach, data were collected through literature reviews, interviews, and observations. Findings reveal that pilgrimages to the Gua Maria provide a profound sense of brotherhood and exemplify genuine tolerance. These sites' openness contributes to national harmony, while the application of Sapta Pesona Wisata (the Seven Charms of Tourism) enhances visitor experiences by emphasising security, comfort, and serenity. This study contributes to religious tourism literature by demonstrating how Sapta Pesona Wisata can improve the quality of Marian pilgrimage tourism, fostering intercultural dialogue and religious tolerance. It underscores the Gua Maria's role in promoting peace, inclusivity, and social cohesion within Indonesia’s pluralistic society.